The first mecp2-null zebrafish model shows altered motor behaviors - Pietri, Thomas; Roman, Angel-Carlos; Guyon, Nicolas; Romano, Sebastián A.; Washbourne, Philip; Moens, Cecilia B.; De Polavieja, Gonzalo G.; Sumbre, German (Frontiers in Neural Circuits, 2013)
Rett syndrome is an X-linked neurodevelopmental disorder and one of the most common causes of mental retardation in affected girls. Other symptoms include a rapid regression of motor and cognitive skills after an apparently early normal development. Sporadic mutations in the transcription factor MECP2 has been shown to be present in more than 90% of the patients and several models of MeCP2-deficient mice have been created to understand the role of this gene. These models have pointed toward alterations in the maintenance of the central nervous system rather than its development, in line with the late onset of the disease in humans. However, the exact functions of MeCP2 remain difficult to delineate and the animal models have yielded contradictory results. Here, we present the first mecp2-null allele mutation zebrafish model. Surprisingly and in contrast to MeCP2-null mouse models, mecp2-null zebrafish are viable and fertile. They present nonetheless clear behavioral alterations during their early development, including spontaneous and sensory-evoked motor anomalies, as well as defective thigmotaxis.